Impact of financing decisions ratios on firm accounting-based performance: Evidence from Jordan listed companies - Feras Izzat Kasasbeh (Future Business Journal, 2021)
The impacts of financing decision ratios on a firm's accounting-based performance are essentially associated with particular data. For this purpose, firm size, firm age, and leverage are taken into account as control variables. The past studies have been reviewed to find gaps, which seemed to incorporate worn-out methods of research, and the inability of past researchers to inculcate firm accounting-based performance while measuring a firm's overall performance. So, data from 40 listed Jordan listed firms from the year 2007 have been collected, and 200 observations are made. The researcher also collected data from the website of the World Bank regarding these firms. It is employed by the generalized movement technique method to avoid heteroscedasticity, autocorrelation, and potential endogenous problems. The study results showed that the impacts of total debt to total assets and short-term debt to total assets are significant and negative on return on assets and return on equity. However, the impacts of long-term debt to total assets are significant and flattering on both return on assets and return on equity. The research has implications for the higher authorities and management to enhance the quality of their financial structure. In contrast, that research has some limitations because of employing a small number of factors to study the impacts of financing decision ratios.
Keywords: 650; Financing decisions ratios; Firm accounting-based performance; Jordan